Synopsis of the genus Paraleuctra (Plecoptera: Leuctridae) from China - Li, Weihai; Wang, Yunbing; Yang, Ding (Zootaxa, 2010)
A species of the family Leuctridae, Paraleuctra tianmushana sp. nov., is described from Zhejiang and Henan, China. Its relationship with closely related species is discussed and a key to Chinese species of Paraleuctra is presented.